Ion beam tracking using ultrasound motion detection. Issue 4 (20th March 2014) - Prall, M.; Kaderka, R.; Saito, N.; Graeff, C.; Bert, C.; Durante, M.; Parodi, K.; Schwaab, J.; Sarti, C.; Jenne, J.
Abstract : Purpose: : The use of motion mitigation techniques such as tracking and gating in particle therapy requires real‐time knowledge of tumor position with millimeter precision. The aim of this phantom‐based study was to evaluate the option of diagnostic ultrasound (US) imaging (sonography) as real‐time motion detection method for scanned heavy ion beam irradiation of moving targets. Methods: : For this pilot experiment, a tumor surrogate was moved inside a water bath along two‐dimensional trajectories. A rubber ball was used for this purpose. This ball was moved by a robotic arm in two dimensions lateral to the heavy ion beam. Trajectories having a period of 3 s and peak to peak amplitude of 20 mm were used. Square radiation fields of 3 × 3 cm 2 were irradiated on radiosensitive films with a 200 MeV/u beam of calcium ions having a FWHM of 6 mm. Pencil beam scanning and beam tracking were employed. The films were attached on the robotic arm and thus moved with the rubber ball. The position of the rubber ball was continuously measured by a US tracking system (Mediri GmbH, Heidelberg) and sent to the GSI therapy control system (TCS). This position was used as tracking vector. Position reconstruction from the US tracking system and data communication introduced a delay leading to a position error of several millimeters. An artificial neural network (ANN) was implemented in the TCS to predict motion from US measurements and thus to compensate for the delay. Results: : Using ANN delay compensation and large motion amplitudes, the authors could produce irradiation patterns with a few percent inhomogeneity and about 1 mm geometrical conformity. Conclusions: : This pilot experiment suggests that diagnostic US should be further investigated as dose‐free, high frame‐rate, and model‐independent motion detection method for scanning heavy ion beam irradiation of moving targets.